Eco-Efficiecy: Are We Converging? - Eduard Nežinský; Martin Hudcovský (European Scientific Journal, ESJ, 2016)
Along with the economic and social indicators, environmental issues constitute one important dimension to be taken into account in assessing the social welfare. There has been a lively discussion about measures of social welfare beyond GDP articulated by Stiglitz Report (Stiglitz et al, 2009) which can be viewed as a summation of the earlier efforts to deal with those challenges. This study concentrates on environmental aspects of economic growth in European countries and the changes undergone in the period of 2000 – 2010. Eco-efficiency is evaluated by non-parametric data envelopment analysis method. Time series of obtained eco-efficiency scores from SBM models were used to infer on the σ-convergence analysed in line with the classical econometric approach. Results show that a process of convergence with respect to eco-efficiency has been taking place in European countries.